Effect of dietary probiotic supplementation on biochemical profile of Murrah buffalo calves - Singh, Naman; jain, Aklank; Roy, Biswajit; Thakur, Mohan Singh (Indian Journal of Animal Production and Management, 2017)
The study was conducted at Livestock Farm Adhartal, NDVSU, Jabalpur for a period of three months. Atotal of 18 murrah buffalo calves of both sexes just after colostrum feeding were selected and divided into3 groups on the basis of their body weight. Group 1 (control) was fed with the basal ration. Group 2 (T1)was fed with the basal ration with probiotic (Saccharomyces cerevisiae) @5g/animal/day and group 3 (T2)was fed with the basal ration with probiotic (Saccharomyces cerevisiae+ Lactobacillus sporogenes) @5g/animal/day. The present study indicated that the total serum protein was significantly (p